KARAKTERISTIK FAKTOR-FAKTOR RISIKO TERJADINYA KOMPLIKASI KRONIK NEFROPATI DIABETIK DAN ATAU PENYAKIT PEMBULUH DARAH PERIFER PADA PENDERITA DIABETES MELLITUS DI RSUD RADEN MATTAHER TAHUN 2018 - Kusdiyah, Erny; Makmur, M. Jufri; Aras, Rudi Berlian Panji (Scientific Of Environmental Health and Diseases, 2021)
ABSTRACT Background : Diabetes mellitus is a chronic disease that can cause complications in the form of diabetic nephropathy and peripheral vascular disease. 35-45% of patient with diabetes mellitus suffered microangiopathic complications of diabetic nephropathy and patient with diabetes mellitus are at risk of 29x complications of peripheral vascular disease followed by nerve disorders, neuropathy, infections, wounds or diabetic ulcers. Method : This study used a descriptive method with a cross sectional . Sampling using purposive sampling technique with 65 samples. Results: In this study, the characteristics of respondents obtained the highest sex of women (56.9%). The age of the majority of respondents was 60-64 years (23.1%). The highest duration of diabetes is ≤5 years (64.6%). The most control of blood sugar levels is uncontrolled (75.4%). Most respondents never exercised (40%). Obesity assessed by the most BMI normoweight (43.2%). Most respondents with a history of regular drug consumption (69.2%). The most types of DM drugs are combinations (80%). Most diets are not controlled (56.9%). Chronic complications of diabetic nephropathy (66.2%). Chronic peripheral vascular complications (33.8%) Conclusion: The most risk factors for chronic diabetic nephropathy complications and or peripheral vascular disease was female sex, age 60-64 years, duration of diabetes mellitus ≤5 years, uncontrolled blood sugar level, never exercising, normoweight, regular drug consumption, combination type of drugs, and uncontrolled diet. Keywords: Diabetes Mellitus, Diabetic Nephropathy, Peripheral Vascular Disease. ABSTRAK Latar belakang: Diabetes mellitus merupakan penyakit kronis yang dapat menimbulkan komplikasi berupa nefropati diabetik dan penyakit pembuluh darah perifer. 35-45% penderita diabetes melitus menderita komplikasi mikroangiopati nefropati diabetik dan penderita diabetes melitus berisiko 29x terjadi komplikasi penyakit pembuluh darah perifer yang diikuti gangguan saraf, neuropati, infeksi, luka atau ulkus diabetik. Metode : Penelitian ini menggunakan metode deskriptif dengan pendekatan cross section. Pengambilan sampel menggunakan tekhnik purpossive sampling dengan 65 sampel. Hasil : Pada penelitian ini karakteristik responden didapatkan jenis kelamin terbanyak perempuan (56,9%). Usia responden terbanyak 60-64 tahun (23,1%). Lama menderita DM terbanyak ≤5 tahun (64,6%). Pengendalian kadar gula darah tidak terkontrol (75,4%). Responden tidak pernah berolahraga (40%). Obesitas yang dinilai dengan IMT normoweight (43,2%). Responden dengan riwayat konsumsi obat teratur (69,2%). Jenis obat DM terbanyak adalah kombinasi (80%). Pola makan tidak terkontrol (56,9%). Komplikasi kronik nefropati diabetik (66,2%). Komplikasi kronik pembuluh darah perifer (33,8%) Kesimpulan : Faktor risiko terbanyak pada komplikasi kronik nefropati diabetik dan atau penyakit pembuluh darah perifer adalah jenis kelamin perempuan, usia 60-64 tahun, lama menderita DM ≤5 tahun, pengendalian kadar gula darah tidak terkontrol, tidak pernah berolahraga, normoweight, konsumsi obat teratur, jenis obat kombinasi, dan pola makan tidak terkontrol. Kata kunci : Diabetes Melitus, Nefropati Diabetik, Penyakit Pembuluh Darah